Analyzing the link between agency problems, governance and control attributes for Pakistan - Ahmad Ghazali; Ahmad Raza Bilal (e-Finanse: Financial Internet Quarterly, 2017)
This research attempts to analyze the relationship between agency, control and corporate gover- nance attributes for a sample of 267 firms listed on the Pakistan Stock Exchange (PSX) from 2005 to 2008. The results show that a) Pakistani listed firms are facing high agency costs problems in contrast to established markets. b) Factors are observed important to having strong effect on miti- gating agency costs levels: corporate dividend policy, degree of board independence, and institu- tional ownership. c) Corporate governance factors reduce discretionary expenditure ratio, increase assets utilization ratio and free cash flow ratio. d) Control variables increases the asset utilization ratio and decreases the free cash flow and increases the managers' performance (Tobin's Q ratio). e) Ownership attributes regulate free cash flow and decrease the discretionary expenditure ratio. The outcomes of this research lead to the proposed use of recommended governance, control and ownership attributes to overcome agency problems and a sound policy for better corporate gover- nance (better management of agency cost issues) for listed firms.
Keywords: G30; G32; 330; corporate governance; performance; agency cost; ownership; pakistan stock exchange